Pharmacokinetics of N‐ethylpentylone and its effect on increasing levels of dopamine and serotonin in the nucleus accumbens of conscious rats. (15th April 2019) - Lin, Zebin; Chen, Yuancheng; Li, Jiaolun; Xu, Zhiru; Wang, Hao; Lin, Junyi; Ye, Xing; Zhao, Ziqin; Shen, Yiwen; Zhang, Yurong; Zheng, Shuiqing; Rao, Yulan
Abstract: N‐Ethylpentylone (NEP) is one of the most confiscated synthetic cathinones in the world. However, its pharmacology and pharmacokinetics remain largely unknown. In this study, the pharmacokentics of NEP in rat nucleus accumbens (NAc) was assessed via brain microdialysis after the intraperitoneal (ip) administration of NEP (20 or 50 mg/kg). The concentrations of dopamine (DA) and serotonin (5‐HT) and their metabolites, including 3, 4‐dihydroxyphenylacetic acid (DOPAC), 3‐methoxytyramine (3‐MT), and 5‐hydroxyindoleacetic acid (5‐HIAA), were simultaneously monitored to elucidate the pharmacological effect of NEP. In addition, the plasma levels of NEP were also assessed. The pharmacokinetics of NEP showed a dose‐related pattern, with NEP rapidly passing through the blood‐brain barrier and reaching a maximum concentration (Cmax ) at approximately 40‐minutes postdose. Approximately 4% of plasma NEP was distributed to the NAc, and considering a homogeneous brain distribution, over 90% of plasma NEP was potentially distributed to the brain. High values of area under curve (AUC) and mean residence time (MRT) of NEP were observed in both the NAc and plasma, indicating large and long‐lasting effects. NEP elicited dose‐related increases in microdialysate DA and 5‐HT and increased the concentration of 3‐MT in a dose‐related manner. However, the rate of DA converted into 3‐MT was unaffected. NEP had a negative effect on the rates of which DA and 5‐HT were transformed into DOPAC and 5‐HIAA, respectively. In summary, NEP rapidly entered the NAc and showed a long‐lasting effect. In addition, DA increased more significantly than 5‐HT, indicating a large potential for NEP abuse. Abstract : N‐Ethylpentylone (NEP) is one of the most confiscated synthetic cathinones in the world. In this study, the pharmacokentics of NEP in rat nucleus accumbens (NAc) was assessed and the concentrations of dopamine (DA) and serotonin (5‐HT) and their metabolites were monitored. We found that NEP rapidly entered the NAc and showed a long‐lasting effect. DA increased more significantly than 5‐HT, indicating a large potential for NEP abuse.